Analysis of Purchasing Decisions and Customer Satisfaction on Sports Equipment Brand MOKS - Fitryana, Destika; Zahwa, Putri; Ula, Masrifatul; Zuniarti, Ida; Basudani, Wahid Akbar (EAJ (Economic and Accounting Journal), 2025)
This study aims to analyze the influence of product quality, brand image, and promotion on purchasing decisions and customer satisfaction for the Moks brand of sports equipment among taekwondo athletes in the Jabodetabek area. Data was collected through a questionnaire distributed to 105 respondents and analyzed using the Structural Equation Model (SEM) with Smart PLS 3.2.9. The results showed that brand image and promotion had a positive and significant influence on purchasing decisions and customer satisfaction, while product quality did not significantly affect purchasing decisions and customer satisfaction. Promotion also had an indirect effect on customer satisfaction through purchasing decisions. These findings highlight the importance of brand strength and effective promotional strategies in increasing customer satisfaction, especially in the competitive sports equipment market. Companies are advised to continue to strengthen their brand image and optimize promotion programs to enhance purchasing decisions and customer satisfaction.